Neuronal death during combined intermittent hypoxia/hypercapnia is due to mitochondrial dysfunction - Douglas, Robert M. (American Physiological Society, 2010)
Breathing-disordered states, such as in obstructive sleep apnea, which are cyclical in nature, have been postulated to induce neurocognitive morbidity in both pediatric and adult populations. The oscillatory nature of intermittent hypoxia, especially when chronic, may mimic the paradigm of ischemia-reperfusion in that tissues and cells are exposed to episodes of low and high O(2) and this may lead to oxidant stress. Therefore, we decided to explore the potential contribution of oxidant stress in our intermittent hypoxia/hypercapnia animal model and the role that mitochondria might play in this stress. Neonatal mice were exposed to intermittent hypoxia/hypercapnia for 10 days and 2 wk. Combined intermittent hypoxia/hypercapnia led to a marked increase in apoptotic cell death in the cerebral cortex. Oxygen consumption studies in isolated mitochondria from intermittent hypoxia/hypercapnia-exposed brains demonstrated significant reductions in both state 4 and state 3 respiratory activities by ∼60% and 75%, respectively. Electron paramagnetic resonance spectroscopy registered a significant increase in superoxide production during nonphosphorylating state 4 by 37%, although superoxide leakage during state 3 did not increase upon treatment. Neuronal superoxide-specific dihydroethidium oxidation was also greater in exposed animals. These studies indicate that intermittent hypoxia/hypercapnia leads to oxidative stress due to mitochondrial response within the mouse central nervous system.